2020
DOI: 10.1007/s00345-020-03359-w
|View full text |Cite
|
Sign up to set email alerts
|

Prospective assessment of two-gene urinary test with multiparametric magnetic resonance imaging of the prostate for men undergoing primary prostate biopsy

Abstract: Purpose To evaluate the diagnostic accuracy of SelectMDx and its association with multiparametric magnetic resonance (mpMRI) in predicting prostate cancer (PCa) and clinically significant PCa (csPCa) on prostate biopsies among men scheduled for initial prostate biopsy. Methods In this single-center prospective study, 52 men scheduled for initial prostate biopsy, based on elevated total PSA level (> 3 ng/ml) or abnormal digital rectal examination, were consecutively included. All subjects underwent SelectMDx, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 23 publications
(29 reference statements)
0
36
0
1
Order By: Relevance
“…Association of different PCa biomarkers with mpMRI findings is another interesting topic worth researching. The combination of biomarkers and mpMRI may result in more clinical benefit than PSA plus mpMRI, especially in those who had equivocal PI-RADS scores (49,57,58). Druskin et al recommended that prostate biopsy be performed in patients with PI-RADS ≥3 lesions in MRI or PHID ≥ 0.44 if PI-RADS score ≤2; this was 100% sensitive for csPCa detection (59).…”
Section: Discussionmentioning
confidence: 99%
“…Association of different PCa biomarkers with mpMRI findings is another interesting topic worth researching. The combination of biomarkers and mpMRI may result in more clinical benefit than PSA plus mpMRI, especially in those who had equivocal PI-RADS scores (49,57,58). Druskin et al recommended that prostate biopsy be performed in patients with PI-RADS ≥3 lesions in MRI or PHID ≥ 0.44 if PI-RADS score ≤2; this was 100% sensitive for csPCa detection (59).…”
Section: Discussionmentioning
confidence: 99%
“…Although this area has benefited from mpMRI, the problem of overdiagnosis and the excessive number of unnecessary biopsies is still debated. In addition to PSA and its derivatives, a large number of new blood and urinary biomarkers to assist in biopsy decisions have appeared in clinical trials, largely thanks to advances in genomic technologies, among which the Prostate cancer antigen 3 (PCA3) [ 20 , 21 ], the SelectMDx multiplex biomarker [ 22 , 23 , 24 ], the ExoDx prostate Intelliscore [ 25 , 26 ], the Prostarix Risk Score [ 27 , 28 ], and the Prostate-specific G-protein coupled receptor (PSGR) [ 29 , 30 ]. However, their contribution in predicting biopsy outcomes needs to be more rigorously weighed.…”
Section: Discussionmentioning
confidence: 99%
“…Van Neste et al postulated that the use of this test could lead to a 42% decrease in the total number of biopsies carried out, with a 53% reduction in the number of unnecessary biopsies [ 172 ]. Further studies have shown that this test can help clinicians identify men at risk of clinically significant PC, thus aiding the initial biopsy decisions and helping to reduce the number of unnecessary biopsies [ 173 , 174 , 175 ]. Analyses have indicated that the use of SelectMDx before proceeding to biopsy could lead to an increase in quality-adjusted life years (a measure of disease burden that takes into account both the quantity and quality of life lived) while also saving healthcare costs [ 176 , 177 , 178 ].…”
Section: Alternative Diagnostic Biomarkers To Psamentioning
confidence: 99%